2019
DOI: 10.1177/2235042x19853382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of multimorbidity among adults in border areas of the Central Highland Region of Vietnam, 2017

Abstract: Introduction: The objectives of this study are to estimate the prevalence of multimorbidity (MM) among adults in the Central Highland Region (a poor region) of Vietnam in 2017 and to identify the sociodemographic correlates of these conditions. Methods: We used data from a cross-sectional study conducted in 2018 on health status among people in four provinces in the Central Highlands Region (Tay Nguyen) of Vietnam. A sample of 1680 adults (aged 15 years and older) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 20 publications
9
17
0
1
Order By: Relevance
“…Although there is a large amount of evidence that the occurrence of multimorbidity is higher in females and at low socioeconomic and educational levels [52], the association with socioeconomic variables is very heterogeneous between studies [53]. As with our results, the lack of association with income [26], education and gender [5] has also been documented. Several factors may be related to these results.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although there is a large amount of evidence that the occurrence of multimorbidity is higher in females and at low socioeconomic and educational levels [52], the association with socioeconomic variables is very heterogeneous between studies [53]. As with our results, the lack of association with income [26], education and gender [5] has also been documented. Several factors may be related to these results.…”
Section: Discussionsupporting
confidence: 77%
“…This reality, aggravated by the reduced supply of health diagnosis and treatment services in rural areas [4], may increase farmers' vulnerability to chronic morbidity. Some evidence suggests worse health conditions and more disease among rural populations compared to other population groups [5,6,7]. It is noteworthy that these diseases may be isolated or coexist in the same individual, a condition known as multimorbidity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Two multi-country studies implemented in different Southeast Asian countries were included in this review [ 14 , 16 ]. Five studies were from Singapore [ 23 , 27 , 34 – 36 ], four studies were from Indonesia [ 24 , 28 , 30 , 31 ], three studies were from Vietnam (all from different parts of Vietnam) [ 15 , 26 , 32 ], two studies were from Thailand [ 33 , 37 ], one was from Myanmar [ 25 ] and one was from Malaysia [ 29 ]. Sample sizes of selected studies ranged from 729 [ 24 ] to 13,798 [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The finding is higher than the rate reported in South Asian countries, India and Pakistan (9.4%), 27 and Bangladesh (8.4%), 28 consistent with the prevalence reported in Canada (12.9%), 13 Switzerland (14.5%) 29 and China (14%) 30 and lower than that of Australia (47.1%), 31 Denmark (39.7%), Brazil (29%), 32 England Open access (27.2%) 3 and Vietnam (16.4%). 33 A systematic review that computed a pooled estimate of multimorbidity from 18 high-income countries and 31 low/middle-income countries had found the prevalence of multimorbidity to be 33.1%. 34 As the prevalence of chronic conditions tends to differ across different countries owing to differences in dietary practices, lifestyle, alcohol consumption, tobacco use and level of physical activity, among others, it is not uncommon for multimorbidity to vary across countries.…”
Section: Discussionmentioning
confidence: 99%
“…9 Likewise, the prevalence of multimorbidity was 14.8% in men and 14.3% in women in Switzerland, 29 and 17.2% in men and 15.5% in women in Vietnam, indicating no disparity in multimorbidity in-between. 33 Multiple studies conducted in different setting have revealed age as a determinant of multimorbidity with the condition being more common with increasing age group. 5 29 38 The prevalence of multimorbidity was 0.81% among participants of age below 30 years and 39.5% among participants of age 75 years or above.…”
Section: Open Accessmentioning
confidence: 99%